Sculpting the skull through neurosensory epithelial–mesenchymal signaling. Issue 1 (24th September 2018) - Yang, Lu M.; Ornitz, David M.
Abstract : The vertebrate skull is a complex structure housing the brain and specialized sensory organs, including the eye, the inner ear, and the olfactory system. The close association between bones of the skull and the sensory organs they encase has posed interesting developmental questions about how the tissues scale with one another. Mechanisms that regulate morphogenesis of the skull are hypothesized to originate in part from the encased neurosensory organs. Conversely, the developing skull is hypothesized to regulate the growth of neurosensory organs, through mechanical forces or molecular signaling. Here, we review studies of epithelial–mesenchymal interactions during inner ear and olfactory system development that may coordinate the growth of the two sensory organs with their surrounding bone. We highlight recent progress in the field and provide evidence that mechanical forces arising from bone growth may affect olfactory epithelium development. Developmental Dynamics 248:88–97, 2019. © 2018 Wiley Periodicals, Inc. Key Findings: Review of epithelial‐mesenchymal interaction during inner ear and olfactory system development.